Analysis of factors related to browning of Dangshan pear (Pyrus spp.) wine. (5th March 2020) - Yang, Hua; Tian, Tiantian; Gu, Hong; Li, Xiaomin; Cai, Guolin; Sun, Junyong; Wu, Dianhui; Lu, Jian
Highlights: DOC was the first factor affecting browning of pear wine. Total phenols was the second factor affecting browning of pear wine. Browning in pear wine was dominated by non-enzymatic browning. OPLS model accurately predicted the browning degree according to the quality index. Abstract: The effects of different dissolved oxygen concentrations (DOC) on the browning degree, amino acids, total phenols, reducing sugars, polyphenoloxidase (PPO), peroxidase (POD), phenylalanine ammonia-lyase (PAL) of pear wine, and the relationship between various quality indicators and browning degree were investigated. Dynamic model fitting analysis of the changes of physiochemical indicators of pear wine in the storage process were performed. The importance of the physiochemical indicators effect on the browning of pear wine during the storage process was analyzed by OPLS (orthogonal partial least squares discriminant analysis), and the effect of dissolved oxygen on the browning of pear wine was systematically revealed. The results showed that dissolved oxygen, total phenols and amino acids had the greatest influence on the browning degree of pear wine. It provided a theoretical basis for revealing the browning mechanism and inhibiting the browning of pear wine.